Germany facing the double crisis in the eurozone: German political discourse in the face of the debt crisis and Covid-19 - Castillo, Jose Manuel (Argumentum, 2021)
The present paper is an analysis of the discourse in European politics leaded by the German authorities in the context of the debt crisis of the eurozone and the Covid-19 crisis. Its objective is to understand the reason for the discursive change carried out by the Government of Angela Merkel. From not accepting the emission of Eurobonds and betting on stricter austerity as a way out of the euro crisis to support the joint emission of debt by the European Commission to finance the recovery plans of the economies most affected by the pandemic crisis. A historical review of the ordoliberal hegemonic conception in German monetary policies, as well as the understanding of the current political-economic context, will demonstrate the real reason for the German discursive change in European politics and its possible continuity in the near future.